Bicycle equity in Brazil: Access to safe cycling routes across neighborhoods in Rio de Janeiro and Curitiba. Issue 1 (2nd January 2018) - Tucker, Bronwen; Manaugh, Kevin
ABSTRACT: In many Latin American cities, rapid motorization and population growth have resulted in unprecedented urban transportation challenges, with lower income populations disproportionately facing constraints to mobility as well as externalities like air pollution, traffic collisions, and the impacts of climate change. The construction of bicycle lane networks has been identified as an effective tool for increasing citizen's mobility and accessibility as well as combating the effects of motorization, but in cities where bicycle lane networks exist, it is not known if they have benefited different income groups equally. This paper assesses the extent to which bicycle lane provisioning has been equitable among neighborhoods in Rio de Janeiro and Curitiba. Both cities were found to have more than twice the supply of bicycle lanes in the wealthiest quintile than the lowest income quintile relative to area and population. A network analysis using a Level of Traffic Stress classification to categorize roads found that wealthier areas have more commercial areas accessible along safer cycling routes. Implications for cycling policy and future research are discussed.